Pricing Mortgage-Backed Securities in a Multifactor Interest Rate Environment: A Multivariate Density Estimation Approach - Boudoukh, Jacob; Whitelaw, Robert F.; Richardson, Matthew; Stanton, Richard (Review of Financial Studies, 1997)
Multivariate density estimation (MDE) suggests that mortgage-backed security (MBS) prices can be well described as a function of the level and slope of the term structure. We analyze how this function varies across MBSs with different coupons. An important finding is that the interest rate level proxies for the moneyness of the option, the expected level of prepayments, and the average life of the cash flows, while the term structure slope controls for the average rate at which these cash flows should be discounted. Though the origination and prepayment behavior of mortgages differ substantially across coupons, there remains an unexplained common factor in MBS prices. This factor does not seem to be related to the usual suspects and therefore presents a puzzle to financial economists.